Isolation, identification, and antibacterial evaluation of endophytic fungi from Gannan navel orange - Wang, Huan; Liu, Ziyue; Duan, Fangfang; Chen, Yan; Qiu, Kaidi; Xiong, Qin; Lin, Huiting; Zhang, Jun; Tan, Haibo (Frontiers in Microbiology, 2023)
In this study, a total of 54 strains of endophytic fungi were successfully isolated from the pulp, peel, twig, and leaf of Gannan navel orange, they were successfully identified to be belonged to 17 species of 12 genera. All these strains were fermented using PDA (potato-dextrose agar) medium, and their secondary metabolites were then extracted with ethyl acetate (EtOAc). The antibacterial assays towards Escherichia coli (E. coli), methicillin-resistant Staphylococcus aureus (MRSA), and Xanthomonas citri subsp. citri (Xcc) were also performed for the EtOAc extracts of these strains. As a result, the extracts of both Geotrichum sp. (gc-1-127-30) and Diaporthe biconispora (gc-1-128-79) demonstrated significant antibacterial activities against Xcc, and the MIC value for the extract of Colletotrichum gloeosporioides against MRSA was low to 62.5 μg/mL. Moreover, the chemical components of the extracts of Colletotrichum sp., Diaporthe biconispora, and Annulohypoxylon atroroseum were primarily investigated, and they successfully led to the isolation of 24 compounds involving a new botryane sesquiterpene. Among the isolated products, compound 2 showed significant inhibitory activities towards SA, MRSA, E. coli, and Xcc with MIC values of 12.5, 3.1, 125, 12.5 μg/mL, respectively. This study revealed that the endophytic fungi of Gannan navel orange showed high potency to produce secondary metabolites with significant antibacterial effects.